Revolutionizing Banking and Finance: The Inexorable Rise of Artificial Intelligence - Herdianti, Fibi Rizki; Yakijan, Deni; Wibasuri, Anggalia (Prosiding International conference on Information Technology and Business (ICITB), 2023)
Since most banking and financial services require the use of technology, the adoption of artificial intelligence (AI) has emerged as one of the major factors influencing the success of financial organizations. In this case, the article delves into the transformative impact of Artificial Intelligence (AI) on the banking and finance sectors, exploring its myriad applications, benefits, challenges, and the future landscape. To do this, we prepared a review of the available literature. 13 journals were examined after a review of several marketing journals from two sources (Mendeley and ScienceDirect) was completed. The publications used for this study were published between 2021 and 2023. Future directions for related study were offered, as well as research implications.Keywords: Artificial Intelligence, Finance, Banking